2019
DOI: 10.31557/apjcp.2019.20.9.2851
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Patched-1 Protein Expression Level in Low Risk and High Risk Basal Cell Carcinoma Subtypes

Abstract: Objective: Basal cell carcinoma (BCC) is the most common malignancy in humans and represents a growing public health care problem. The major etiological factors contributing to BCC development are exposure to ultraviolet radiation and genetic alterations. BCC is primarily caused by dysregulation of sonic Hedgehog (HH) signaling pathway in basal cells of the skin. BCC can be classified into low risk non-aggressive and high risk aggressive subtypes. BCC subtypes differentiation is essential for prognosis and for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 38 publications
1
13
1
Order By: Relevance
“… 25 Also, Almomani et al found that the correlation between low-risk or high-risk BCC subtypes and the PTCH1 expression level was not statistically significant. 26 We found that the intensity of IHC staining for PTCH1 was higher in superficial BCC than other subtypes, although this difference was not significant. We speculate that this may be related to the anatomical location of superficial BCC, where more superficial tumors have a higher mutational burden or are more likely to accumulate UV-associated mutations.…”
Section: Discussioncontrasting
confidence: 55%
“… 25 Also, Almomani et al found that the correlation between low-risk or high-risk BCC subtypes and the PTCH1 expression level was not statistically significant. 26 We found that the intensity of IHC staining for PTCH1 was higher in superficial BCC than other subtypes, although this difference was not significant. We speculate that this may be related to the anatomical location of superficial BCC, where more superficial tumors have a higher mutational burden or are more likely to accumulate UV-associated mutations.…”
Section: Discussioncontrasting
confidence: 55%
“…Inactivating mutations of PTCH1 and SMO, occur in 90% and 10%, respectively of basal cell carcinoma. 16 Somatic mutations arise due to the effects of ultraviolet radiation to DNA within basaloid keratinocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Recent publications have tried to elucidate the genetic profiles of BCC subtypes. 16 , 25 , 26 , 27 There has been a strong association identified between expression of the PTCH1 gene in low‐risk tumours (i.e., nodular and superficial) compared to high‐risk tumours (i.e., micronodular and infiltrative), although this was not found to be statistically significant. 16 A more recent study looked specifically at low‐risk BCCs including nodular and superficial variants and found that both the NOTCH1 and PTCH1 gene were more frequent in superficial than nodular BCCs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevoid basal cell carcinoma syndrome (NBCCS) is an autosomal dominant disorder characterized by mutations in the patched ( PTCH ) 1 gene, PTCH2 gene and suppressor of the fused ( SUFU ) gene, which are negative regulators of the hedgehog (Hh) pathway [ 8 ]. PTCH1 , located on chromosome 9q22.3, encodes the homologous transmembrane protein PTCH1 that acts as a receptor for the Hh pathway [ 9 ]. PTCH2 is located on chromosome 1p34 and encodes for PTCH2 and SUFU is located on chromosome 10q24.32 and encodes for the suppressor of a fused homologous protein, SUFU [ 8 ].…”
Section: The Genetic Basis Of Basal Cell Carcinoma Initiation and mentioning
confidence: 99%